The Persistence of Profitability: A Dynamic Panel Data Analysis of Indonesian Public Companies - Suwandaru, Agung; Filfilan, Assaf Z.; Mahatma Ratri, Anandhayu; Efendi, Alvin Ramadhan Putra; Kurniawan, Cahya Nova; Firdaus, Muhammad Rizki (Relevance: Journal of Management and Business, 2025)
This study analyzes the dynamics of profitability for Indonesian public companies, focusing on the persistence of profits and the roles of leverage and firm size. Using a dynamic panel data analysis with a System GMM estimator on data from 44 firms over 24 years, the findings reveal a lack of profitability persistence, indicating that high profits are short-lived in this competitive market. Furthermore, financial leverage has a strong negative impact on profitability, while firm size shows no significant effect. These results suggest that managers should focus on continuous innovation and maintain a conservative debt policy, and that investors should not rely on past performance as a predictor of future returns. The study provides evidence that sustainable advantage in Indonesia stems from factors beyond mere scale or financial leverage.